THE INFLUENCE OF FINANCIAL INCLUSION ON MSMES PERFORMANCE IN BADUNG REGENCY - I Made Yogiarta; Ni Nyoman Suriani; L.G.P. Sri Eka Jayanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study aims to identify the effect of financial inclusion on the performance of Micro, Small and Medium Enterprises (MSMEs) in Badung Regency. In this study, data was collected from 100 respondents who are owners or stakeholders of MSMEs in the region. Survey methods with questionnaires were used to collect data, and descriptive statistical analysis and regression were carried out to analyze the relationship between financial inclusion variables and MSME performance. The results showed that financial inclusion has a significant positive influence on the performance of MSMEs in Badung Regency. Easier access to financial services, such as banking, credit, and insurance, provides MSMEs with opportunities to increase working capital, production, and business capacity. In addition, financial inclusion programs also contribute to the reduction of financial risk and the improvement of managerial skills, which support the growth and sustainability of MSMEs. This research implies that the implementation of financial inclusion policies can be a key factor in improving the economic welfare of MSMEs in Badung Regency. Therefore, continuous efforts are needed from the government, financial institutions, and related parties to strengthen adequate financial support and infrastructure, as well as involve MSMEs in training programs to maximize the benefits of financial inclusion in supporting the growth of the MSME sector in Badung Regency.